Reduction of the Early Autogenous Shrinkage of High Strength Concrete - Drago Saje (Advances in Materials Science and Engineering)
The results of a laboratory investigation on the early autogenous shrinkage of high strength concrete, and the possibilities of its reduction, are presented. Such concrete demonstrates significant autogenous shrinkage, which should, however, be limited in the early stages of its development in order to prevent the occurrence of cracks and/or drop in the load-carrying capacity of concrete structures. The following possibilities for reducing autogenous shrinkage were investigated: the use of low-heat cement, a shrinkage-reducing admixture, steel fibres, premoistened polypropylene fibres, and presoaked lightweight aggregate. In the case of the use of presoaked natural lightweight aggregate, with a fraction from 2 to 4 mm, the early autogenous shrinkage of one-day-old high strength concrete decreased by about 90%, with no change to the concrete's compressive strength in comparison with that of the reference concrete.